Chicken litter-derived catalyst for persulfate activation to remove acetaminophen: An organic-waste-to-wealth strategy - Yang, Heejin; Joo, Junghee; Hong, Eunmi; Park, Seong Jik; Lee, Jechan; Lee, Chang Gu (Chemical Engineering Journal, 2023)
Extracting value from organic waste (e.g., chicken litter) to deliver high-end products should become an essential disposal strategy in the future. Herein, chicken litter was employed as the feedstock to produce a catalyst for peroxydisulfate (persulfate) activation for potential wastewater treatment applications. Three different chicken litter samples were prepared to investigate the effects of inorganic species contained in chicken litter on the catalyst performance: (1) chicken litter without pretreatment, (2) chicken litter washed with 0.05 M HCl, and (3) chicken litter washed with 0.25 M HCl. When the chicken litter-derived catalyst was used for persulfate activation, acetaminophen (ACP) was effectively removed, suggesting a synergic effect. When utilizing the catalyst derived from chicken litter without undergoing HCl pretreatment, the degradation efficiency of ACP reached 84.1%, surpassing that of the pretreated catalysts. The ACP degradation efficiency further improved to 93.8% and 93.9% with increased catalyst dose and persulfate concentration. The reactive oxygen species present during the ACP degradation were analyzed using chemical scavengers. O2•− radicals showed a dominant effect on ACP degradation. ACP degradation was greatly suppressed when HCO3− and humic acid coexisted. Furthermore, combustible byproducts of the catalyst production process can be potentially used to supply energy to the process, which would help lower the overall energy requirement.
Keywords: Analgesic degradation; Chicken litter; Degradation efficiency; High end Products; Organic wastes; Persulfate activations; Pre-treatments; Waste to wealth; Waste valorizations; ]+ catalyst; Analgesics degradation; Organic waste; Persulfate activation; Waste treatment; Waste valorization